IMPLEMENTASI KEBIJAKAN PENGEMBANGAN PARIWISATA DI KABUPATEN GAYO LUES - Maharami Maharami; Edy Putra Kelana; Faizal Madya (Universitas Bina Taruna Gorontalo, 2024)
This research aims to analyze how tourism policy is implemented in Gayo Lues Regency and what factors influence the implementation of tourism policy. This research uses a qualitative descriptive research approach with data collection techniques, namely interviews, observation and documentation studies. The research was conducted referring to Merille S. Grindle's policy implementation theory. The results of the research conducted show that the implementation of tourism development policies in Gayo Lues Regency has not been optimal. There are several supporting and inhibiting factors for policy implementation. The supporting factors are that the interests affected by the policy are shared interests, not personal interests, the type of benefit produced has multiple effects so that its scope can be felt by various groups, the characteristics of the governing body which continues to carry out activity programs in accordance with existing policies, the compliance and responsiveness of the implementers. Very good. Meanwhile, the inhibiting factors are that the degree of change expected in tourism development policy is not the degree of change that can be achieved in a short time, the location of decision makers and policy implementers and targets is relatively far so that implementation does not run optimally, there are implementers of tourism development policy programs who have tourism education backgrounds. , the resources involved in the form of human resources, physical resources, technological resources and financial resources in Gayo Lues Regency are very minimal, the actors involved do not have a high commitment in making tourism development strategies.